Penerapan Laporan Keuangan Berdasarkan SAK EMKM Berbasis Microsoft Excel pada Kanein Food di Jatirasa, Bekasi - Elan Kurniawan; Muhammad Affar; Rianto Rianto; Alvina Dwi Octaviani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: This study aims to help Kanein Food prepare financial reports based on SAK EMKM using an excel-based system, so that the preparation of financial reports becomes more effective. Method: The type of research used in this research is qualitative research. Source of data used in this research is primary data. Result: This study show that the preparation of financial reports prior to implementing the system at Kanein Food was still done manually and the recording was still general in nature. After implementing the system, the preparation of financial reports becomes more administrative and tidy, the preparation of financial reports also saves time because the results of financial reports appear automatically. Based on the results of testing the effectiveness of the system, the test produces an average value of 8 which means it is effective. It can be concluded that this system makes the preparation of financial reports at Kanein Food more effective and efficient. Limitation: Tthe number of respondents is only business owners and one employee who are both trained objects until they are proficient in operating the Microsoft Excel financial reporting application with contributions between the assistant and the mentor experiencing positive benefits in applying the Excel accounting software and can be sustainable.